Pelagic protected areas: the missing dimension in ocean conservation - Game, Edward T.; Grantham, Hedley S.; Hobday, Alistair J.; Pressey, Robert L.; Lombard, Amanda T.; Beckley, Lynnath E.; Gjerde, Kristina; Bustamante, Rodrigo; Possingham, Hugh P.; Richardson, Anthony J. (Trends in ecology & evolution (Amsterdam), 2009)
Fewer protected areas exist in the pelagic ocean than any other ecosystem on Earth. Although there is increasing support for marine protected areas (MPAs) as a tool for pelagic conservation, there have also been numerous criticisms of the ecological, logistical and economic feasibility of place-based management in the dynamic pelagic environment. Here we argue that recent advances across conservation, oceanography and fisheries science provide the evidence, tools and information to address these criticisms and confirm MPAs as defensible and feasible instruments for pelagic conservation. Debate over the efficacy of protected areas relative to other conservation measures cannot be resolved without further implementation of MPAs in the pelagic ocean.